Propagation and Molecular Characterization of Bioreactor Adapted Very Virulent Infectious Bursal Disease Virus Isolates of Malaysia. (2nd September 2018) - Lawal, Nafi'u; Hair-Bejo, Mohd; Arshad, Siti Suri; Omar, Abdul Rahman; Ideris, Aini
Abstract : Two Malaysian very virulent infectious bursal disease virus (vvIBDV) strains UPM0081 (also known as B00/81) and UPM190 (also known as UPM04/190) isolated from local IBD outbreaks in 2000 and 2004, respectively, were separately passaged for 12 consecutive times in 11-day-old specific pathogen free (SPF) chicken embryonated eggs (CEE) via the chorioallantoic membrane (CAM) route. The CEE passage 8 (EP8) isolates were passaged once in BGM-70 cell line yielding UPM0081EP8BGMP1 and UPM190EP8BGMP1, while the EP12 isolates were passaged 15 times in BGM-70 cell line yielding UPM0081EP12BGMP15 and UPM190EP12BGMP15 using T25 tissue culture flask. These isolates were all propagated once in bioreactor using cytodex 1 as microcarrier at 3 g per liter (3 g/L) yielding UPM0081EP8BGMP1BP1, UPM190EP8BGMP1BP1, UPM0081EP12BGMP15BP1, and UPM190EP12BGMP15BP1 isolates. The viruses were harvested at 3 days after inoculation, following the appearance of cytopathic effects (CPE) characterized by detachment from the microcarrier using standard protocol and filtered using 0.2  μ m syringe filter. The filtrates were positive for IBDV by RT-PCR and immunofluorescence. Sequence and phylogenetic tree analysis indicated that the isolates were of the vvIBDV strains and were not different from the flask propagated parental viruses.